2015
DOI: 10.1118/1.4918576
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a MOSkin detector for in vivo skin dose measurements during interventional radiology procedures

Abstract: The MOSkin detector proved to be reliable when exposed to different field sizes, SSDs, depths in solid water, dose rates, frame rates, and radiation incident angles within a clinical x-ray beam. The MOSkin detector with water equivalent depth equal to 0.07 mm is a suitable detector for in vivo skin dosimetry during interventional radiology procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The derived MOSFET sensitivity was 14.88 and 15.77 mV/cGy for measurement with and without bowtie filter, respectively. This indicated a minimal sensitivity variation within 6% for blank and filtrated beam qualities, which is consistent with the previous finding [22]. The possible reason is that the filtration changes the energy spectrum and the high atomic number material in the sensitive volume of the MOSFET (silicon oxide) tends to over respond to the low energy x-rays due to photoelectric absorption effects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The derived MOSFET sensitivity was 14.88 and 15.77 mV/cGy for measurement with and without bowtie filter, respectively. This indicated a minimal sensitivity variation within 6% for blank and filtrated beam qualities, which is consistent with the previous finding [22]. The possible reason is that the filtration changes the energy spectrum and the high atomic number material in the sensitive volume of the MOSFET (silicon oxide) tends to over respond to the low energy x-rays due to photoelectric absorption effects.…”
Section: Discussionsupporting
confidence: 90%
“…The physical performance of this dosimeter was well documented in the literature for external beam radiotherapy [27, 28], interventional radiology procedures [22] and diagnostic radiology dosimetry [16, 17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been applied when using radiation detectors known to be energy dependent when used under kV photon beams. 22 , 33 The energy dependence of the radiation detectors calibrated under the clinical beams would be much lesser within the energy range used. Brown et al 34 reported a relative sensitivity of 3% for EBT3 film used under 25–35 keV monochromatic beams.…”
Section: Discussionmentioning
confidence: 99%
“…The increased interest in small-animal radiation biology research has resulted in a requirement for improvements in the standardized dosimetry of pre-clinical irradiations [1], [2,3]. In vivo dose measurement can be accomplished using devices like MOSFET-based dosimeters [4][5][6], Gafchromic films [7], or silica-based fibres as thermoluminescent dosimeters (TLDs) [8][9][10][11][12][13][14]. Computational techniques using mathematical models of systems can also be used to calculate radiation doses.…”
Section: Introductionmentioning
confidence: 99%